2009
DOI: 10.1029/2009gl037276
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect impacts of Saharan dust acting as cloud condensation nuclei on tropical cyclone eyewall development

Abstract: The mechanisms by which Saharan dust acting as cloud condensation nuclei (CCN) impact tropical cyclone (TC) evolution were examined by conducting numerical simulations of a mature TC with CCN added from lateral boundaries. CCN can affect eyewall development directly through release of latent heat when activated and subsequent growth of cloud droplets and indirectly through modulating rainband development. Convection in the rainbands was negatively correlated with that in the eyewall in all simulations. The dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 16 publications
8
61
0
Order By: Relevance
“…The centers of all grids and that of the storm were approximately coincident (∼15 • N, 40 • W). The corresponding time steps were 60, 20, and 2.5 s. The idealized TC simulations were similar to those of Zhang et al (2007Zhang et al ( , 2009) except for recent updates in the model. For this study we implemented a prognostic scheme (based on the O' Dowd diagnostic formulae (1997) to take into account sea-spray sources for the film, jet, and spume modes which act as CCN and GCCN, respectively.…”
Section: Model Configuration and Experimental Designsupporting
confidence: 54%
See 3 more Smart Citations
“…The centers of all grids and that of the storm were approximately coincident (∼15 • N, 40 • W). The corresponding time steps were 60, 20, and 2.5 s. The idealized TC simulations were similar to those of Zhang et al (2007Zhang et al ( , 2009) except for recent updates in the model. For this study we implemented a prognostic scheme (based on the O' Dowd diagnostic formulae (1997) to take into account sea-spray sources for the film, jet, and spume modes which act as CCN and GCCN, respectively.…”
Section: Model Configuration and Experimental Designsupporting
confidence: 54%
“…For instance, other mechanisms could be preventing a rapid intensification of the storm provided the simulated invigoration of convective activity in the outer rainbands (see Bister, 1997Bister, , 2001). Sublimation of ice crystals could also be playing a non negligible role; however, Zhang et al (2007Zhang et al ( , 2009) performed a heating analysis that led to the conclusion that the main response was at low-levels. Riemer et al (2010) also finds evidence that the invigoration of convective activity in the outer rainbands leads to a reduction in TC intensity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al (2007) found that dust could act as CCN and induce changes in the hydrometeor properties, modifying the latent heat distribution and ultimately influencing the storm intensity through complex dynamical processes. In a more recent work, Zhang et al (2009) showed that dust could indirectly affect the eyewall development by modifying the latent heat release in rainbands. Both studies note that more detailed observational information on Saharan dust microphysical properties and vertical distributions is needed to further develop a mechanistic understanding of the potential effects of dust on hurricane genesis and intensity.…”
mentioning
confidence: 99%